Word, Self, and Silence in Samuel Beckett - Loran Gami (Current Swedish Archaeology, 2022)
The article focuses on the relationship between language and self in Samuel Beckett and explores how the writer both represents and undermines the concept of self as contingent on words. Issuing from the ego and ultimately leading to the ego, language in Beckett is arbitrary and tautological, and solipsism seems to be the inevitable result. Beckett shares a deep skepticism of language with such philosophers as Fritz Mauthner and Ludwig Wittgenstein. It is however difficult, if not outright impossible, to determine the degree of influence that their ideas might have had on Beckett. Rather than rigorously using them as theoretical bases which might serve as a key to ‘unlocking’ Beckett, the article eclectically makes use of them, seeing them as springboards for a better understanding of his work. The article also discusses how Beckett transcends the idea of solipsism. In his plays and prose works there is a radical annihilation of the self, and the concept of a unified ego is undermined. Several characters/narrators/voices speak with a voice they cannot claim as their own and often they do not even relate to themselves with the pronoun ‘I’. Since language is an arbitrary and inadequate system, silence seems to be the inevitable result and, possibly, escape.